Tanggung Jawab Keperdataan Terkait Wanprestasi Pasal 7 Huruf F UU No. 8 Tahun 1999 Tentang Perlindungan Konsumen - Randi Randi (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Civil liability related to default gives consequences to the seller or service provider, where the consumer has the right to ask for compensation or fulfillment of the rights agreed in the contract. The purpose of this research is to examine civil liability related to default in Article 7 Letter F of Law no. 8 of 1999 concerning Consumer Protection. In this study the authors used normative juridical legal research methods, by giving the main role to the study of documents and comprehensive analysis of secondary data. Civil liability related to default provides protection to consumers in the face of unfair business practices and strengthens the enforcement of consumer rights. With this provision, Law no. 8 of 1999 provides a strong legal basis for consumers to demand compensation or fulfillment of their rights in the event of default.